Correlation between smoking and neovascularization in biceps tendinopathy: a functional preoperative and immunohistochemical study - Jan Zabrzynski; Maciej Gagat; Lukasz Paczesny; Dariusz Grzanka; Gazi Huri (SAGE Publishing, 2020)
Aims: The purpose of this study was to investigate whether smoking is associated with neovascularization in the tendinopathy of the long head of the biceps tendon (LHBT). Methods: The study included 40 consecutive patients who underwent arthroscopic biceps tenotomy/tenodesis due to chronic biceps tendinopathy and divided into three groups: (1) non-smokers, (2) former smokers, (3) smokers. LHBT tissue samples were stained with H&E, Alcian blue and Trichrome staining. Immunohistochemical examination was performed using anti-CD31 and anti-CD34. The neovessel density score (NDS) was scored by Bonar criteria. Results: The mean period of smoking was 15.50 years with an average number of 24 cigarettes/day in the former smokers and 21.69 years with an average number of 15 cigarettes/day in the active smokers. The mean NDS was 2.23/3 in non-smokers, whereas it was 1.60/3 in former smokers and 1.31/3 in active smokers. The mean American Shoulder and Elbow Surgeons score equaled 46 in never smoked patients, 43.60 in former smokers, and 41.46 in active smokers. In the patients with smoking history, the disorganized tendinous tissue islands were avascular and composed of compact acidic polysaccharides and mucopolysaccharides. We observed negative correlation between the NDS and the smoking indexes, including cigarettes per day ( p  = 0.0150), smoking years ( p  = 0.0140), pack-years ( p  = 0.0088). Conclusion: In conclusion, the present study revealed that smoking impairs the vascularization of the biceps tendon in chronic tendinopathy. Clinically, we observed a negative correlation between smoking and neovascularization. Furthermore, there was no correlation between neovascularization and functional preoperative status.